Large-scale ordered magnetic fields generated in mergers of helium white dwarfs - Pakmor, Rüdiger; Pelisoli, Ingrid; Justham, Stephen; Rajamuthukumar, Abinaya S.; Röpke, Friedrich; Schneider, Fabian; Mink, Selma E. de; Ohlmann, Sebastian T.; Podsiadlowski, Philipp; Morán Fraile, Javier; Vetter, Marco; Andrássy, Róbert (Astronomy and astrophysics, 2024)
Stellar mergers are one important path to highly magnetised stars. Mergers of two low-mass white dwarfs may create up to every third hot subdwarf star. The merging process is usually assumed to dramatically amplify magnetic fields. However, so far only four highly magnetised hot subdwarf stars have been found, suggesting a fraction of less than 1%. We present two high-resolution magnetohydrodynamical (MHD) simulations of the merger of two helium white dwarfs in a binary system with the same total mass of 0.6 M⊙. We analysed an equal-mass merger with two 0.3 M⊙ white dwarfs, and an unequal-mass merger with white dwarfs of 0.25 M⊙ and 0.35 M⊙. We simulated the inspiral, merger, and further evolution of the merger remnant for about 50 rotations. We found efficient magnetic field amplification in both mergers via a small-scale dynamo, reproducing previous results of stellar merger simulations. The magnetic field saturates at a similar strength for both simulations. We then identified a second phase of magnetic field amplification in both merger remnants that happens on a timescale of several tens of rotational periods of the merger remnant. This phase generates a large-scale ordered azimuthal field via a large-scale dynamo driven by the magneto-rotational instability. Finally, we speculate that in the unequal-mass merger remnant, helium burning will initially start in a shell around a cold core, rather than in the centre. This forms a convection zone that coincides with the region that contains most of the magnetic energy, and likely destroys the strong, ordered field. Ohmic resistivity might then quickly erase the remaining small-scale field. Therefore, the mass ratio of the initial merger could be the selecting factor that decides if a merger remnant will stay highly magnetised long after the merger.